Teoretičnì problemi obġruntuvannâ pravovih oznak socìal′noї dopomogi u sferì socìal′nogo zabezpečennâ - Sinčuk, Svìtlana (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The author investigates the essential and specific features of social benefits in the sphere of social security. These are the single monetary form and the purpose of social provision. For the first time the purpose of the appointment is argued to be the criterion for the differentiationof social benefits.
Keywords: pomoc społeczna na Ukrainie; pomoc społeczna; zagadnienia teoretycznoprawne